Современные модели управления государственным долгом (финансовый и правовой аспекты) - Калгина, Александра; Цареградская, Юлия (Вопросы государственного и муниципального управления, 2018)
Financial and legal aspects in the formation of models of national debt management in the Russian Federation have become a topic of research. Having shown that the current state of legal regulation in national debt management is not effective due to the lack of legislative adherence to this concept and failure to take advantage of the various organizational models of national debt management, the authors offer a number of suggestions for the improvement of the budget legislation regulating questions of national debt management. A definition is given to the concept of “national debt management” and its standard and legal adherence in the Budget code of the Russian Federation and also three models of national debt management – traditional, alternative and mixed – are entered. National debt management is understood as a set of financial actions of the state represented by its authorities on the regulation of the size, structure and cost of servicing central government debt, and which are carried out at the strategic and tactical levels with use of a set of legal methods of regulation. It is pointed out that it is necessary to take into account the optimum scenario of social and economic development of the state – target (forced), infl uencing efficiency in national debt management. In practice, it has been proved that it is necessary to use the international experience in the sphere of national debt management, namely, to transform the traditional model of management into alternative, allowing it to exercise similar control of the independent subject, combining powers of public authority and fi nancial economic entity. As a similar subject, Vnesheconombank of Russia is offered. The importance of the interrelation of national debt management model with methods of central government debt management is emphasized.